Policing nightlife areas: comparing youths’ trust in police, door staff and CCTV - Brands, Jelle (Policing and society, 2020)
Against a background of the pluralisation of policing in contemporary city spaces, and sustained interests in the assessment of policing in the criminology and criminal justice literatures, the current study seeks to draw a comparative analysis in trust between policing actors, as experienced by nightlife consumers. While studies on trust in the police are numerous, this is much less the case for other actors involved in policing urban (nightlife) spaces. Neither is it very well understood how trust is distributed between policing actors. It is important to investigate this, taking into consideration the privatisation and technologisation of safety provision in contemporary cities, and the legitimacy of the actors involved. Using a survey, 894 youths enrolled in education were asked to evaluate their trust in actors involved in the policing of urban nightlife areas: the police, door staff, and CCTV. Results showed that people tend to trust human policing agents more compared to technological agents. A cluster analysis further indicated that alongside this general pattern, four additional groups can be found in the data: two groups that display the highest trust in either the police or door staff with intermediate trust in CCTV, and two groups expressing either overall low trust or overall high trust, independent of the policing actor. Employing logistic regression analyses, we find that demographic, victimisation, and contextual variables predict cluster membership. We end with suggestions for future research and reflect on whether the privatisation and technologisation of (nightlife) policing are desirable from a nightlife consumer point of view.